Are Younger CEOs Better for Sustainability? Moderating Roles of Education and Experience in Emerging Markets - Ria Karina; Teddy Jurnali; Anderson Anderson; Erna Wati (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the effect of young Chief Executive Officer (CEO) on sustainability performance and investigate the moderating roles of CEO education and experience. Methodology: This study employs a quantitative research approach using panel data from companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample consists of 189 companies that published annual and sustainability reports, resulting in 128 firm-year observations that were analyzed using StataMP 17 and panel regression analysis. Results: The findings show that young CEOs do not directly improve sustainability performance. However, CEO education and international experience strengthen their ability to implement sustainability-oriented strategies. Conclusions: This study concludes that the effectiveness of young CEOs in enhancing sustainability performance depends on the quality of their managerial human capital, particularly their education and international experience. These findings support the Upper Echelons Theory by demonstrating that executive characteristics shape sustainability-related strategic decisions. Limitations: This study may face selection bias because it only includes firms that published both annual and sustainability reports during 2019–2023, potentially excluding less-transparent firms. In addition, the use of quantitative methods limits the deeper exploration of qualitative factors such as CEO values, stakeholder pressure, and organizational culture. Contributions: This study extends Upper Echelons Theory by examining the moderating effects of CEO education and international experience on the relationship between young CEOs and sustainability performance. The findings provide practical insights for firms and policymakers in developing effective sustainability leadership strategies.